Pengaruh Pemberian Ibuprofen Preoperatif Terhadap Sebaran Sel Radang Kronis Pada Proses Penyembuhan Luka Pasca Pencabutan Gigi - Fanny Marisca Alviony; Eddy Hermanto; Widaningsih (Denta Journal Kedokteran Gigi, 2016)
Background: Wound is destruction of part of the body's tissues caused by agent like germs, parasites, fungi, sharp force trauma, temperature changes, chemicals, electric shock. Inflammatory phase in the process of wound healing has very important role. In the chronic inflammation there are chronic inflammatory cell infiltration, namely macrophages, lymphocytes, plasma cells, eosinophils, mast cells, basophils accompanied by the proliferation of blood vessels and fibrosis. Ibuprofen is anti-inflammatory and analgesic drugs that usually given after tooth extraction. Purpose: This study was aimed to examine the effect of preoperative ibuprofen against the spread of chronic inflammatory cells in the process of wound healing after tooth extraction. Materials and Methods: The experimental unit used were 20 male Wistar rats divided into two groups, group1 (NaCMC 0.2%), group2 (Ibuprofen 7,2mg / 200grBB). NaCMC 0.2% for the group K and Ibuprofen for group X given 1 hour before incisor tooth extraction and then the bottom left tooth of mice were be lifted. The Socket were then sutured and left up to 7 days. Data were analyzed by Chi-Square test. Results: Chi-Square test showed significant difference between group K and X p = 0.003 (p <0.05). Conclusion: Preoperative administration of ibuprofen were lower the spread of chronic inflammatory cells in the process of wound healing after tooth extraction.